The Dialectics of Environment and Arabic Literature: Representations in Literary Discourse and the Role of Contemporary Writing in Promoting Environmental Awareness - Kassem, Alia (Journal of Cultural Analysis and Social Change, 2025)
The current research aimed to clarify the status of the environment in Arabic literature, to clarify the nature of the environment's influence on writers and their literary texts, and to identify the role of contemporary Arabic literature in raising environmental awareness and addressing contemporary environmental issues. To achieve the research objectives, the historical approach was used to clarify the impact of the environment across different eras, starting with the pre-Islamic era and focusing specifically on the current era. The descriptive-analytical approach was also used, presenting some poetic examples to clarify the relationship between Arabic literature and environmental awareness, framing the idea and topic of the research. The results concluded that environmental literature was able to reflect the environmental conditions in which humans live, as the environment represents the stimulus from which writers derive their vocabulary and literary texts. The results also confirmed that literary texts provided an expressive description of the environment and emphasized the reciprocal relationship between humans and the environment. Recent literary texts succeeded in highlighting environmental issues, especially in light of the ongoing developments and changes the world is witnessing, including issues related to climate change, desertification, air and water pollution, unjust practices in exploiting natural resources, wars, and others. Highlighting these issues in Arabic literature would enhance environmental awareness and reduce the effects of negative practices. Moreover, the results indicated that mention of the environment in literary texts is still contained within the general framework of general texts, where the environment represents a means to serve the artistic purposes of literary works; however, it is not an end in itself. What the world needs at the present era is an accelerated level of awareness of the negative impact of humans on the environment in the current era. This may direct literary writings to re-read previous Arabic texts and move from them towards a new approach that shifts the literary text to new horizons that support peaceful aspects of environmental conservation. The study recommended the necessity of adopting effective language in presenting images that enhance awareness of environmental conservation, including aesthetic imagery, humanistic narration, and simulation.